Experiences of nurses providing maternity care in a public hospital during the COVID-19 pandemic in Nepal: A qualitative study - Bidhya Basnet; Pratiksha Chapagain; Sabitra Subedi; Tulasha Dahal; Saraswati Neupane; Ranjita Khanal; Richard J. Pinder; Don Eliseo Lucero-Prisno; Shyam Sundar Budhathoki (Public Library of Science (PLoS), 2022)
Maternity service providers have struggled to provide high-quality services to women and newborns during the ongoing COVID-19 pandemic which has substantially impacted health systems and disrupted maternity services globally. Nepal is a resources-limited country that reported a significant impact of the pandemic on maternal health services. It is therefore important to understand better the perspective of health care professionals in this context. This study intends to explore the experiences of nurses providing maternity care in the public sector during the COVID-19 pandemic in Nepal. A qualitative study using a phenomenological design was conducted. Altogether ten nurses working in maternity services were selected using purposive sampling technique. Data were collected by face-to-face in-depth interviews using a semi-structured interview guide. Thematic analysis was conducted using Clarke and Braun 2006 technique. The findings of the study were organized into codes, sub-themes and themes. The six themes identified were fear of COVID-19 at work, challenges at work, changes at work and services, motivations to work, stigma due to COVID-19, and impact on services. Participants described how maternity services could not be stopped during the pandemic. They had experienced decreased utilization of antenatal services as a consequence of 'lockdown' thereby leading to an increase in maternal and neonatal mortality. Respondents reported ineffective human resource management compromising the quality of care. The professional responsibility to cope with adverse circumstances and serve society is a major source of motivation that health workers relied upon to get them through the pandemic period. A wide range of challenges were faced by service providers during the pandemic which requires action and support of all levels of government, institutions and society-at-large to assure the continued provision of safe maternity care during such a protracted period of challenging work.